Formulation and Investigation of CK2 Inhibitor-Loaded Alginate Microbeads with Different Excipients - Boglárka Papp; Marc Le Borgne; Florent Perret; Christelle Marminon; Liza Józsa; Ágota Pető; Dóra Kósa; Lajos Nagy; Sándor Kéki; Zoltán Ujhelyi; Ádám Pallér; István Budai; et al. (MDPI AG, 2023)
The aim of this study was to formulate and characterize CK2 inhibitor-loaded alginate microbeads via the polymerization method. Different excipients were used in the formulation to improve the penetration of an active agent and to stabilize our preparations. Transcutol® HP was added to the drug-sodium alginate mixture and polyvinylpyrrolidone (PVP) was added to the hardening solution, alone and in combination. To characterize the formulations, mean particle size, scanning electron microscopy analysis, encapsulation efficiency, swelling behavior, an enzymatic stability test and an in vitro dissolution study were performed. The cell viability assay and permeability test were also carried out on the Caco-2 cell line. The anti-oxidant and anti-inflammatory effects of the formulations were finally evaluated. The combination of Transcutol® HP and PVP in the formulation of sodium alginate microbeads could improve the stability, in vitro permeability, anti-oxidant and anti-inflammatory effects of the CK2 inhibitor.